2011
DOI: 10.1007/s10840-011-9585-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein electrophysiology during cryoballoon ablation as a predictor for procedural success

Abstract: This study, the largest to date, showed that real-time monitoring of PV conduction during cryoballoon freezing can be safely performed with a circular mapping catheter. A cutoff time of 83 s to PV isolation was predictive of sustained procedural PV isolation success without reconduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 18 publications
1
35
3
Order By: Relevance
“…9,14 Detailed information is provided in the Appendix in the Data Supplement. In a subgroup of patients, an ET probe (SensiTherm, St. Jude Medical, Saint Paul, MN) was used.…”
Section: Ablation Procedures and Verification Of Pvimentioning
confidence: 99%
See 2 more Smart Citations
“…9,14 Detailed information is provided in the Appendix in the Data Supplement. In a subgroup of patients, an ET probe (SensiTherm, St. Jude Medical, Saint Paul, MN) was used.…”
Section: Ablation Procedures and Verification Of Pvimentioning
confidence: 99%
“…15 Recently, we have published data on predictors for intraprocedural reconduction using the first CB generation. 9 The cutoff TTI for predicting a stable PVI was 83 seconds. A new predictive cutoff TTI for procedural success with CBG2 cannot be calculated because of the low number of reconducting veins with CBG2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Dorwarth et al demonstrated that sustained PVI was associated with a shorter mean time to conduction block (39 seconds) when compared to PVs with recovered PV conduction (125 seconds) [43]. The authors identified a cut-off time of 83 seconds for the prediction of stable sustained PVI without reconduction (86% sensitivity and 97% specificity).…”
Section: How To Perform Cryoballoon Ablationmentioning
confidence: 99%
“…In contrast to the relatively high rate of procedural reconnection observed in studies of RF-based AF ablation (up to 50% in some series), the rate of acute reconnection post CBA appears to be low. In studies employing waiting periods of up to 60 minutes, the pooled rate of acute recurrence among the 749 treated PVs was <1% [40,43,46-48]. Moreover, in contrast to RF-based ablation, the use of adjunctive pharmacologic agents such as adenosine and/or isoproterenol does not appear to provide additional prognostic information in patients undergoing CBA [40,49,50].…”
Section: How To Perform Cryoballoon Ablationmentioning
confidence: 99%